The Royal Marsden manual of clinical nursing procedures - Lister, Sara E.; Hofland, Justine; Grafton, Hayley (Hoboken, NJ : Wiley-Blackwell, 2020)
"". . . an excellent resource to improve and enhance clinical practice." Nursing Standard ". . . a worldwide oracle' for all clinical nursing procedures." Cancer Nursing Practice "Any nurse. . . will find a good reason to dip into this book at some time." Nursing Times ". . . a pleasure to read and difficult to put down." Emergency Nurse Now in its tenth edition, The Royal Marsden Manual of Clinical Nursing Procedures has been the definitive, market-leading guide to clinical nursing skills for over three decades. This internationally best-selling title sets the gold standard for nursing care; providing the procedures, rationale, and guidance required by qualified nurses to deliver clinically effective, patient-focused care with expertise and confidence. With over two-hundred detailed procedures, this comprehensive manual presents the evidence and underlying theory alongside full-colour illustrations and photographs, and includes coverage of infection prevention and control, perioperative care, wound management, nutrition, diagnostic testing, discharge, medicines management, and much more. Loved and trusted by millions for over thirty years, The Royal Marsden Manual of Clinical Nursing Procedures continues to be a truly indispensable guide for nursing practice. Written by nurses for nurses. Empowers nurses to become informed, skilled practitioners. Reflects current procedures and changes in modern adult nursing practice. All procedures are supported by up to date evidence, including detailed rationales for each step of each procedure. Considers the clinical governance around the procedures and nursing practice"--
The context of nursing and the introduction -- Admissions and assessment -- Discharge care and planning -- Infection prevention and control -- Communication, psychological wellbeing and safeguarding -- Elimination -- Moving and positioning -- Nutrition and fluid balance -- Patient comfort and supporting personal hygiene -- Pain assessment and management -- Symptom control and care towards the end of life -- Respiratory care, CPR and blood transfusion -- Diagnostic tests -- Observations -- Medicines optimisation - ensuring quality and safety -- Perioperative care -- Vascular access devices : insertion and management -- Wound management -- Self-care and wellbeing.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Nursing Care -- methods; Nursing Process; Nursing Theory; Patient Care Planning